Strategi Pengelolaan Perpustakaan Umum Kota Madiun dalam Meningkatkan Minat Baca dan Literasi Masyarakat - Intan Faiza Susanto; Rosta Alanawa Intan Hanafiah; Bilfa Yumna Zalfi Licia (Universitas PGRI Madiun, 2026)
This study aims to analyze the management strategy of the Madiun City Public Library in increasing reading and literacy among the public post-COVID-19 pandemic. Using a qualitative approach with descriptive methods, data collection was conducted through in-depth interviews with librarians, direct observation, and documentation. The results show that the library's organizational structure is under the auspices of the Madiun City Library and Archives Service, which is divided into three strategic areas. The library implements the Dewey Decimal Classification (DDC) classification system in compiling collections managed using INLIS Lite software from the National Library. To address the decline in post-pandemic visits, the library launched various integrated innovative programs such as the